Fluid-fluid Levels in Musculoskeletal Tumor Imaging - Tsukamoto, Shinji; Errani, Costantino; Facchini, Fabio; Papagelopoulos, Panayiotis; Mavrogenis, Andreas F. (Current Medical Imaging, 2021)
Fluid-fluid levels result from the separation of two fluids of differing densities within a cavernous space with the boundary between the two layers running in a horizontal plane at 90 degrees to the direction of gravity. Magnetic resonance imaging is the most sensitive imaging modality to identify fluid-fluid levels. Although the most common bone lesions containing fluid-fluid levels are aneurysmal bone cyst and telangiectatic osteosarcoma, fluid-fluid levels can be observed in a wide variety of bone and soft tissue lesions. Therefore, fluid-fluid levels cannot be considered diagnostic of any particular type of tumor and the diagnosis should be made on the basis of other clinical, radiological and pathological findings. This article summarizes the pathophysiology and imaging characteristics of fluid-fluid levels and discusses the differential diagnosis of tumors with this imaging sign.
Keywords: imaging